Pencegahan Kejadian Ventilator-Associated Pneumonia (VAP) dengan Kepatuhan Pelaksanaan Bundle: Literature Review - Solikin Solikin; Matius Sakundarno Adi; Septo Pawelas Arso (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Prevention of Ventilator-Associated Pneumonia (VAP) Events with Compliance with Bundle Implementation: Literature Review Background: Patients who experience critical illness and use a mechanical ventilator in the ICU have an increased risk of experiencing ventilator associated pneumonia (VAP) which is a major cause of morbidity and mortality in the ICU and causes lengthening the length of stay and an increase in hospital costs.Purpose: To conduct a recent literature review with regard to VAP primarily related to causes, risk factors, pathogenesis, prevention, early detection and diagnosis, and administration of antibiotics to patients with VAP. At the end of this article conclusions will be presented that can be used by practitioners as a clinical guide.Method: The design used was literature review, articles were collected using a search engine, including (Clinicalkey) 27 articles, (Cochrane) 25 articles, (Medline) 17 articles and (Pubmed) 19 articles. From the predetermined article inclusion criteria, we found 7 articles out of 88 that were suitable for different interventionsResults: Prevention of VAP incidents in hospitals using multimodal interventions, one of which is the application of a VAP prevention bundle, can effectively reduce the incidence of VAP in hospitals. Examination of the lower respiratory tract culture should be carried out for all patients before administering antibiotic therapy provided that it should not delay giving antibiotic therapy to critical patients. Early treatment of broad-spectrum antibiotics with the right dosage can maximize the efficacy of antibiotics and the outcome of VAP patients in the ICU. Antibiotic combinations must be used wisely to treat VAP because certain pathogens increase the life expectancy of patients with severe infections especially those with septic shock. Negative culture results can also be used to stop antibiotic therapy in patients undergoing culture without antibiotic changes within the last 72 hours. The health team must consider the need for antibiotic de-escalation based on the culture results and the clinical response of the patient.Conclusion: VAP prevention bundles that implement multimodal interventions effectively reduce the incidence of VAP in hospitals. An examination of airway culture must be carried out for all patients before administering antibiotic therapy. Early treatment of broad-spectrum antibiotics can maximize the efficacy of antibiotics and the outcome of VAP patients in the ICU.Keywords: VAP; ICU; Patients; Morbidity; Mortality; BundlePendahuluan: Pasien yang mengalami penyakit kritis dan menggunakan ventilator mekanik di ICU mempunyai peningkatan resiko untuk mengalami ventilator associated pneumonia (VAP) yang merupakan penyebab utama morbiditas dan mortalitas di ICU serta menyebabkan pemanjangan lenght of stay dan peningkatan biaya rumah sakit.Tujuan: Untuk melakukan review literature terkini sehubungan dengan VAP terutama terkait dengan penyebab, faktor resiko, pathogenesis, pencegahan, deteksi dini dan diagnosis, serta pemberian antibiotik pada pasien dengan VAP. Di ahir artikel ini akan disampaikan kesimpulan yang dapat digunakan praktisi sebagai panduan di klinis.Metode: Desain yang digunakan adalah literature review, artikel dikumpulkan menggunakan mesin pencarian antara lain (Clinicalkey) 27 artikel, (Cochrane) 25 artikel, (Medline) 17 artikel dan (Pubmed) 19 artikel. Dari kriteria inklusi artikel yang telah ditentukan, ditemukan 7 artikel dari 88 yang sesuai dengan intervensi yang berbeda.Hasil: Pencegahan kejadian VAP di rumah sakit menggunakan intervensi multimodal, yang mana salah satunya berupa penerapan bundle pencegahan VAP, dapat dengan efektif menurunkan kejadian VAP di rumah sakit. Pemeriksasan kultur saluran nafas bawah perlu dilakukan kepada semua pasien sebelum pemberian terapi antibiotik dengan catatan tidak boleh menunda pemberian terapi antibiotik pada pasien kritis. Terapi dini antibiotik spektum luas dengan dosis yang tepat dapat memaksimalkan kemanjuran antibiotik dan luaran pasien VAP di ICU. Kombinasi antibiotik harus digunakan dengan bijaksana untuk mengobati VAP karena pathogen tertentu untuk meningkatkan harapan hidup pasien dengan infeksi berat terutama yang mengalami shok sepsis. Hasil kultur yang negatif juga dapat digunakan untuk menghentikan terapi antibiotik pada pasien yang dilakukan kultur tanpa perubahan antibiotik dalam 72 jam terahir. Tim kesehatan harus mempertimbangkan perlunya deeskalasi antibiotik berdasarkan hasil kultur dan respon klinik pasien.Simpulan: Bundle pencegahan VAP yang menerapkan intervensi multimodal efektif menurunkan kejadian VAP di rumah sakit. Pemeriksasan kultur saluran nafas harus dilakukan kepada semua pasien sebelum pemberian terapi antibiotik. Terapi dini antibiotik spektum luas dapat memaksimalkan kemanjuran antibiotik dan luaran pasien VAP di ICU.